2014
DOI: 10.1186/1471-2318-14-40
|View full text |Cite
|
Sign up to set email alerts
|

Fall risk-increasing drugs and falls: a cross-sectional study among elderly patients in primary care

Abstract: BackgroundFalls are the most common cause of injuries and hospital admissions in the elderly. The Swedish National Board of Health and Welfare has created a list of drugs considered to increase the fall risk (FRIDs) and drugs that might cause/worsen orthostatism (ODs). This cross-sectional study was aimed to assess FRIDs and their correlation with falls in a sample of 369 community-dwelling and nursing home patients aged ≥75 years and who were using a multi-dose drug dispensing system.MethodsData were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 33 publications
10
123
1
8
Order By: Relevance
“…Hence, the prevalence of consumption patterns in this demographic sector should be carefully monitored, mainly regarding health promotion and disease prevention, which are activities inherent to the PHC service team in the Family Health Strategy. (3,8,10,16) In this study, the association between religiosity and alcohol and tobacco consumption patterns is in line with other studies in this field. (5,6) In brief, the presence of religiosity (evaluated by the dimensions of organizational and intrinsic religiosity) seemed to have a protective effect on the consumption of alcohol and tobacco.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, the prevalence of consumption patterns in this demographic sector should be carefully monitored, mainly regarding health promotion and disease prevention, which are activities inherent to the PHC service team in the Family Health Strategy. (3,8,10,16) In this study, the association between religiosity and alcohol and tobacco consumption patterns is in line with other studies in this field. (5,6) In brief, the presence of religiosity (evaluated by the dimensions of organizational and intrinsic religiosity) seemed to have a protective effect on the consumption of alcohol and tobacco.…”
Section: Discussionsupporting
confidence: 92%
“…These data are similar to those found in studies performed at this health care level in Brazil. (10,14,15) As regards religion, there was a significant percentage of Catholics and Evangelicals; these data are shown in the 2010 Brazilian census and other studies about the Brazilian population profile. (16) The association between female sex and higher consumption of alcohol is in line with national and international studies (3,(17)(18)(19) that described the global increase in alcohol consumption among women in the last few years.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Data has shown that polydrug use is considered a powerful risk factor not only for falls but also for fractures among the elderly 23 , although this finding is not unanimous among studies 26 . The use of certain medications, such as opioids, antipsychotics, anxiolytics, hypnotics and antidepressants, may be associated with the presence of symptoms which can influence the occurrence of falls, such as dizziness, instability and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The questionnaires consist of 6 parts: Part A was about socio-demographic characteristics such as gender, age, race, marital status, educational level. Part B was about the health status include weight, height, BMI, blood pressure and random blood sugar.…”
Section: Methodsmentioning
confidence: 99%